A PROTOTYPE DEVICE FOR PRODUCING FRESH WATER FROM ATMOSPHERIC AIR - O. V. Evdulov; I. A. Gabitov; K. S. Gyulmagomedov; D. N. Kobzarenko; A. I. Semilyak (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives.The aim of the article is to develop the design and carry out the physical and mathematical modelling of a device for producing fresh water from atmospheric air in coastal areas, as well as under the conditions of sea transport.A Method for constructing the device for producing fresh water from atmospheric air is developed on the basis of a physical and mathematical model. Fresh water is obtained by condensation on a cold surface, which dew point is created using the natural cold of seawater with the application of the energy of moving waves for its circulation. The heating of the surface air layer adjacent to the cold surface by solar concentrators intensifies the process of the moisture condensation.Results. Data is obtained on the quantity (mass) of fresh water produced per unit of condensation surface area (1 m2 ) for 1 hour depending on the temperature difference between the condensation surface and seawater. The influence of the characteristics of solar concentrator and liquid heat remover with seawater on the device parameters is studied.Conclusion. It is established that the amount of the fresh water obtained from atmospheric air strongly depends on the temperature difference between the condensation surface and seawater. Thus, according to calculations, with an increase of the latter by 45 K, the mass of fresh water obtained from a condensation surface of 1 m2 in 1 hour approximately doubles to 5.8 kg.